Impacted Mandibular Third Molars Associated Pathologies - Sadia Sahibzada, Ajmal Khan, Tariq Sardar, Usama Aurangzeb, Nafeesa Afridi, Intikhab Amanat (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: The purpose of this research was to identify the most common and severe types of pathologic diseases surrounding impacted mandibular third molars using radiographic imaging. Cases and procedures: An analysis of past patients who had impacted mandibular molars extracted at Oral & Maxillofacial Surgery of Cat D Hospital Gara Tajik Peshawar. Impacted mandibular third molar radiographic lesions, patient age and gender were used as the study’s outcome measures. Caries, pericoronal radiolucent areas, periapical radiolucent areas, odontomes, and external resorption of the roots of adjacent mandibular second molars were also noted on radiographs of the impacted third molar. Histopathology confirmed the presence of bone marrow in all radiolucent regions. Results: There were 2,832 mandibular third molars that had been impacted and were studied from 1,397 individuals; 49.4 percent of the impacted teeth had associated radiographic abnormalities. Dental cavities were the most prevalent abnormality detected by panoramic radiography. Other examples of this type of radiolucency can be found at the periphery of the cortex and at the tip of the apex. Histological analysis confirmed that chronic periapical inflammation was the primary cause of most periapical radiolucent regions. Histological examination revealed that all radiolucent spots located around the corona were malignant cysts or tumours. Dentigerous cysts were the most common type of cyst, while ameloblastomas were the most common type of tumour. Conclusion: A large proportion of the patients with a third molar impaction in the mandible also had an underlying pathologic condition. Keywords: Mandibular, Radiolucent, Panoramic, Tumor